Local communities' perceptions towards economic impacts from ecotourism development in Klim Karst Geoforest Park, Langkawi - Ahmad, Nurul Azwa; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
The tourism development in Kilim Karst Geoforest Park (KKGP) in Langkawi has brought many changes to the local community. These changes regarded as an important benefit to them. A household survey based on sample of 302 respondents in 3 villages around KKGP and a face to face was conducted in for 2 weeks. A Factor analysis was carried out to identify the respondents’ perception of economic impacts from ecotourism development in KKGP. Finding from data analysis show positive perceptions towards ecotourism development, it has been group into 6 factors which explained for 40% of variance extracted from 56 variables in the data namely: 1. Income Opportunities, 2. Entrepreneurial Opportunities, 3. Community Facilities, 4. Benefits to woman and youth, 5. Qualified boat operators, 6.Cottage industry from ecotourism development. Finally finding from data analysis show that ecotourism development bring more economic benefits towards local community, but if the development were carried out without properly strategy and planning, could influence perception local community vice versa. On the others hands the local authorities are responsible to plays as a vital role to bring a successful tourism development in KKGP and to maintain the increasing number of tourist that will keep coming to the destination and at the same time local community be able to get benefit from it.